Structural and Transport Properties of Epitaxial Niobium-Doped BaTiO3 Films - Shao, Yang (My University, 2009)
Highly orientated BaTi1-xNbx03 thin films, spanning the entire range of x, have been successfully deposited on (001) MgAl20 4 substrates by the pulsed laser deposition (PLD) method. The structure of the films is characterized with a range of techniques. It is found that increasing x gives rise to a Ti4+ to Ti3+ transformation in the oxidation state accompanied by increased conductivity with a semiconductormetal transition near x = 0.2. Temperature dependent magnetic measurements show an anomalous rise in the spin moment. In order to further reduce the lattice mismatch and keep the conductivity at the same time, a partial strontium-for-barium substitution, (Ba1-ySry)Ti0.5Nb0.5O3 withy = 0, 0.4, 0.5 and 0.6, were used. Such a substitution provides a means for independently tuning the lattice parameter and conductivity over a significant range of compositions. The y = 0.6 composition show a sharp interface with flawless epitaxy and good quality films. We attribute the improvements in the film quality to a decrease in the lattice misfit strain made possible through the superior lattice match to the substrate obtained through strontium substitution. Electronic structure calculations were carried out by the 1st principle method using the WIEN2k program in order to understand the electronic structure of these compounds. Based on the assumed ordered structures, the Fermi level of BaTi1-xNbxO3 gradually moved to the lower energies as x increase, while the valence bands were not significantly altered with the Nb ions substitutions. The fraction of each Ti4+ and Ti3+ component in BaTi1-xNbxO3 samples was extracted by the linear profile fitting of the corresponding Ti-L2,3 edge obtained by the electron energy loss spectra. The fitting results indicate a high fraction of Ti3+ is present than excepted as Nb content increase, which could arise from the loss of oxygen stoichiometry. The electron energy loss spectra of the 0-K edge is analyzed by comparison to the partial density of states calculation. The evolutions of 0-K edge features are explained in terms of the decrease of the Ti 3d band contribution and the increase of the Nb 4d band contribution as the Nb content increase.
Keywords: BaTi, thin films, substrates, conductivity, epitaxy, electron, energy